Correlations between angular velocities in selected joints and velocity of table tennis racket during topspin forehand and backhand - Bankosz, Z.; Winiarski, S. (Journal of Sports Science & Medicine, 2018)
The aim of this study was to determine the correlations between angular velocities in individual joints and racket velocity for different topspin forehand and backhand strokes in table tennis. Ten elite female table tennis players participated, presenting different kinds of topspin forehands and backhands - after a no-spin ball (FH1, BH1), after a backspin ball (FH2, BH2) and "heavy" topspin (FH3, BH3). Range of motion was measured with the BTS Smart-E (BTS Bioengineering, Milan, Italy) motion analysis system with a specially developed marker placement protocol for the upper body parts and an acoustic sensor attached to the racket to identify ball-racket contact. In forehand strokes angular velocities of internal arm rotation and adduction in shoulder joint correlated with racket velocity. Racket velocity was correlated with angular velocities (hip extension on the playing side; hip flexion on the opposite side; ankle flexion) in the case of a topspin forehand performed with maximal force -"heavy" topspin (FH3). In backhand strokes the velocities of arm abduction and shoulder girdle rotation towards the playing side correlated with racket velocity. The angular velocity of internal arm rotation and adduction in shoulder joint may be important components of a coordinated stroke, whilst angular velocity can substantially affect the racket speed when one is changing the type of stroke